A multi-center, open label, single group, observational clinical trial to investigate the effects of training on the administration of Cardioplexol™ - Tevaearai Stahel, Hendrik T.; Taheri, Niuscha; Winkler, Andreas; Hohlfeld, Johannes; Dietl, Wolfgang; Starck, Christoph; Van Linden, Arnaud; Bidovec, Jan; Imhof, Aaron; Carrel, Thierry P.; Voet, Bernard; Walther, Thomas; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCardioplexol™ was recently proven effective and non-inferior to Buckberg's solution in a pivotal Phase-3 clinical trial. We hypothesized here that a standardized training program for surgeons without prior experience of Cardioplexol™ could increase its administration reliability and participate to its overall benefit.MethodsOpen label, single group, observational study involving 29 surgeons from 7 centers in 3 countries. The training program included a theoretical part, and two surgical procedures performed under trainer supervision. In a subsequent evaluation part, surgeons operated on 4 additional patients. The number of major deviations from the pre-defined administration protocol (incorrect volume of initial/second/third/fourth dose, incorrect duration of injection of initial dose, incorrect timing of application of initial/second/third/fourth dose) was set as primary endpoint.ResultsA total of 171 patients were screened of which 157 were operated on (57 in the training part and 100 in the evaluation part). No major deviations were observed. Other outcomes, including postoperative TnT and CK-MB profiles, cumulative inotropic support provided during the first 24 h after myocardial reperfusion, cardiac conversion rate, ICU length of stay, were all similar to or better than the results observed in the previous pivotal study.ConclusionCardiac surgeons not familiar to Cardioplexol™ benefit from a structured and supervised training. This kind of training contributes to improve the efficiency and safety of a new cardioplegic solution such as Cardioplexol™.Trial registration[ClinicalTrials.gov]: identifier [NCT03823521, and EudraCT No: 2018-002311-10].